Televisi Publik: Kajian tentang Opini Masyarakat Kota Bandung mengenai TV Publik - Sabur, Betty RF (Mediator, 2008)
This research was aimed to analyze several aspects of Public TV in its preparation phase. The focus is directed toward socialization, cognition, judgment, aspirations, and contributions of Public TV to the people of Bandung City. By employing analytical descriptive as methods to addressing research questions, about 250 respondents were asked to fill questionnaires. In-depth interviews to prominent members of society, media experts, and others related with such problems were also carried out. The research has led to some findings, e.g. cognition and judgment levels socialization is on average. The most important thing for the public, considering the importance of Public TV, is the dominant functions of Public TV to represent education and cultural programs. If managed by  idealism toward education and leveraging people’s quality, Public TV would create a positive image for itself.